SharePoint 2010 Userʼs Guide : Learning Microsoftʼs Business Collaboration Platform - Bates, Seth (Apress, 2013)
SharePoint 2010 is the next stage in the evolution of the SharePoint technology platform. SharePoint 2010 expands on the previously provided SharePoint platform by extending existing capabilities and introducing new capabilities to make it easier and more cost effective to create business collaboration solutions. We have seen many situations where SharePoint is introduced and individuals struggle to leverage these resources because they are not aware of all the capabilities available or how to leverage them to gain the most value possible. This book was an outcome of this need and can serve as a reference for people working within a SharePoint environment.